2013
DOI: 10.1167/iovs.12-11239
|View full text |Cite
|
Sign up to set email alerts
|

Subretinal Implantation of Retinal Pigment Epithelial Cells Derived From Human Embryonic Stem Cells: Improved Survival When Implanted as a Monolayer

Abstract: hESC-RPE can survive for at least 12 months in an immunocompromised animal model. Polarized monolayers of hESC-RPE show improved survival compared to cell suspensions. The lack of teratoma or any ectopic tissue formation in the implanted rats bodes well for similar results with respect to safety in human subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
246
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(252 citation statements)
references
References 34 publications
5
246
0
1
Order By: Relevance
“…There was also no evidence of a local inflammatory response or peri-implant fibrosis in any of the eyes. In line with an earlier study we conducted in rats [12], no formation of teratoma or ectopic tissue was observed in the minipig eye. Immunohistochemistry for TRA-1-85 and RPE65 was positive in all of the CPCB-RPE1 implants, indicating that the hESC-RPE cells survived in those samples after 1 month of implantation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There was also no evidence of a local inflammatory response or peri-implant fibrosis in any of the eyes. In line with an earlier study we conducted in rats [12], no formation of teratoma or ectopic tissue was observed in the minipig eye. Immunohistochemistry for TRA-1-85 and RPE65 was positive in all of the CPCB-RPE1 implants, indicating that the hESC-RPE cells survived in those samples after 1 month of implantation.…”
Section: Discussionsupporting
confidence: 91%
“…The advantages of the surgically foldable MSPS carrier include customized macular shape in diameter and thickness [8], ultrathin parts with diffusion [7], and excellent RPE adherence [10,11] and survival [12], whereas its nondegradability and unknown long-term effects can be seen as disadvantages. The study criteria for successful implantation were appropriate placement of the implant in the subretinal space, as assessed by OCT and post-mortem histology.…”
Section: Discussionmentioning
confidence: 99%
“…This is done either by unrolling a sheet of RPE cells underneath the retina through a slit, or by growing the cells on an artificial porous substrate and inserting both the cells and prosthetic into the subretinal space. The advantages of these techniques are obvious as the RPE cells do not need to "repolarize" upon implantation, and the potential formation of pigmented spheres of RPE cells that escape into the retina can be largely avoided 16,44 . However, these surgical techniques are inherently even more complicated.…”
Section: Sub-retinal Injection (~5 Min Per Injection)mentioning
confidence: 99%
“…This will avoid prolonging experiments in animals where engrafted cells are incorrectly placed, under immune attack, or have died early in the experimental protocol. Although conventional in vivo imaging (rodent ophthalmoscopy) allows for some initial confirmation of subretinal bleb formation, 9,24,25 implying transplantation to the correct retinal layer, it is ineffective at determining subretinal graft presence past the day of transplantation. This is because ophthalmoscopy views the retina en face, making blebs of smaller profile harder to identify; moreover, aside from host erythrocytes (in cases where subretinal hemorrhaging occurs), graft and host cells cannot be differentiated through the neural retinal.…”
Section: Real-time Detection Of Graft Placement and Survivalmentioning
confidence: 99%
“…25,[28][29][30][31] However, the performance of these materials cannot be assessed in vivo using standard imaging techniques. A recent (2014) study, implanting a monolayer of RPE attached to a ridged polyester scaffold, utilized a similar approach to our bimodal imaging to help address this very limitation.…”
Section: Monitoring Biomaterials Efficacy In Generating Optimal Graft mentioning
confidence: 99%